1976
DOI: 10.1007/bf00428693
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in sympathetic-adrenal medullary reactions induced by different stressors

Abstract: Male and female university students were exposed to two different stressors in each of two 110-min sessions, i.e., a cognitive task (color-word conflict) and repeated venipuncture. Catecholamine excretion, heart rate, and subjective reactions were measured. Control values were obtained under conditions of relaxation in the laboratory. Subjects of both sexes responded to both stressors by increased heart rate and feelings of unpleasantness and distress. The pattern of adrenaline excretion, however, differed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(31 citation statements)
references
References 16 publications
1
27
1
2
Order By: Relevance
“…The sexually dimorphic behaviour during stress has been related to fundamental physiological differences between males and females. For example, a study in humans found that males secrete higher levels of adrenaline when compared to females of the same age while exposed to identical stressors [9]. Sex differences in response to stress in rats have also been identified [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The sexually dimorphic behaviour during stress has been related to fundamental physiological differences between males and females. For example, a study in humans found that males secrete higher levels of adrenaline when compared to females of the same age while exposed to identical stressors [9]. Sex differences in response to stress in rats have also been identified [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Severe or episodic hypertension seen in 90% of pheochromocytoma patients has not been observed as a feature of TCBS. Men seem to produce higher levels of plasma catecholamines in response to emotional stress and are more sensitive to catecholamine mediated vasoconstriction than women 43,44 ; but women are far more commonly affected. Recurrences are rare with repetitive or worsening stress.…”
Section: Pathophysiology and Mechanismsmentioning
confidence: 98%
“…Część badań wskazuje na brak różnic międzypłciowych, a część na wyższe bazowe stężenia katecholamin u mężczyzn (Zouhal i in., 2008). Efekt ten tłumaczy się tym, iż dla mężczyzn świadomość nadchodzących testów stanowi większy stresor niż dla kobiet (Frankenhaeuser, Dunne, Lundberg, 1976). W badaniach wykorzystujących pomiary katecholamin należy zatem zwracać szczególną uwagę na ewentualne różnice międzypłciowe.…”
Section: Katecholaminy W Organizmie Człowiekaunclassified